(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
The purpose of this study is to theorize a human rights-based approach to the protection of future generations, by focusing on the role that climate litigation is playing before international human rights judicial and quasi-judicial bodies and domestic courts. After exploring the most significant legal sources and cases, this study theorizes the potential role of climate litigation in paving the way to the justiciability of the protection of future generations, by defining specific States’ obligations – including extraterritorial duties – and promoting a human rights-based framework, capable of incorporating intergenerational equity, environmental justice, sustainable development, consistently with the precautionary principle.